2013
DOI: 10.1002/hyp.10095
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of hydraulics transport time scales within the Arvand River estuary, Iran

Abstract: Transport time scales are key parameters for understanding the hydrodynamic and biochemical processes within estuaries. In this study, the flushing and residence times within the Arvand River estuary have been estimated using a two-dimensional hydrodynamic model called CE-QUAL-W2. The model has been calibrated and verified by two different sets of field data and using the k-ε vertical eddy diffusivity scheme. Flushing time has been estimated using different methods such as the tidal prism and fraction of fresh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…4). These results showed that the model worked at a satisfactory level, compared with the similar numerical studies carried out in this area (e.g., Mahab-Sweco 1976; Parsa et al 2007;Etemad-Shahidi et al 2014).…”
Section: Calibration and Verification Of The Modelsupporting
confidence: 67%
“…4). These results showed that the model worked at a satisfactory level, compared with the similar numerical studies carried out in this area (e.g., Mahab-Sweco 1976; Parsa et al 2007;Etemad-Shahidi et al 2014).…”
Section: Calibration and Verification Of The Modelsupporting
confidence: 67%
“…The Arvand River-also known as Shatt-al-Arab-is one of the longest tidal rivers on the border of Iran-Iraq which is formed by the conjunction of the Tigris and Euphrates rivers in Iraq and Karun River in Iran (Figure 1b) [44]. Three major cities, Abadan, Khoramshahr, and Basra, are located around it (Figure 1b), with the river running mainly towards the south to reach the Persian Gulf [45]. Before discharging into the Persian Gulf (Figure 1c), the river varies from 270-2500 m in width and 9-15 m in depth, which implies that it is navigable.…”
Section: Study Areamentioning
confidence: 99%